Pulicaria vulgaris Gaertn. essential oil: an alternative or complementary treatment for Leishmaniasis - Sharifi-Rad, Mehdi; Salehi, Bahar; Sharifi-Rad, Javad; Setzer, William N; Iriti, Marcello (Cellular and Molecular Biology, 2018)
Leishmaniasis is a neglected parasitic protozoal disease that affects approximately 12 million people and represents a public health problem in Iran. The objectives of this study were to obtain the essential oil (EO) from Pulicaria vulgaris Gaertn. growing in Iran and to carry out in-vitro antileishmanial screening of the EO against promastigotes of Leishmania major and Leishmania infantum. The EO from the aerial parts of P. vulgaris was extracted by hydrodistillation. Serial dilutions of the EO were screened for in-vitro antileishmanial activity using 96-well microtiter plates. The P. vulgaris EO was active against the promastigote forms of L. major and L. infantum, with IC50 values of 244.70 and 233.65 µg/mL, respectively. Pulicaria vulgaris EO may serve as an alternative or complementary treatment for leishmaniasis.